Na-doping effects on structural evolution and superconductivity in (K1−xNax)2Cr3As3 (x = 0–1). (22nd March 2019) - Mu, Qing-Ge; Ruan, Bin-Bin; Pan, Bo-Jin; Liu, Tong; Zhao, Kang; Chen, Gen-Fu; Ren, Zhi-An
Abstract: In this report, we studied the effects of isovalent Na-doping on the recently discovered quasi-one-dimensional Cr-based unconventional superconductor K2 Cr3 As3 . A series of polycrystalline samples with nominal component (K1− x Na x )2 Cr3 As3 ( x   =  0–1) were synthesized by the solid state reaction method. From crystal structure and chemical phase characterizations, we found two distinct chemical phases with the same hexagonal structure but distinguished by different site occupancy of Na + ions at the two kinds of K-site in the K2 Cr3 As3 lattice structure. When x   ⩽  0.4, the doped samples form a continuous sosoloid phase of (K1− x Na x )2 Cr3 As3 with the Na + ions randomly doping at the K-sites (denoted as α -phase); when x   ⩾  0.5, a novel individual phase of (K0.25 Na0.75 )2 Cr3 As3 emerges, in which the Na + ions selectively occupy all the '3k' sites and the K + ions occupy the '1c' sites (denoted as β -phase). No chemical phase of Na2 Cr3 As3 was detected. Superconductivity in these samples was studied by electrical transport and magnetic susceptibility measurements, and it evolves in a much sophisticated manner. In the α -phase, the superconducting T c decreases quickly upon Na-doping. All these α -phase samples have surprisingly low superconducting volume fraction and relatively low T c compared with the undoped K2 Cr3 As3 . However, the β -phase has a clearly enhanced T c up to 7.6 K which locates between the values of K2 Cr3 As3 and Na2 Cr3 As3, and exhibits a full superconducting shielding signal.